Teaching the History of Human Rights and "Humanitarian" Interventions - Nolan, Mary (Radical Teacher, 2015)
This article explores how I teach about human rights and so-called humanitarian interventions to MA and Ph.D. students.  The course has three main themes or foci.  First, what are human rights and why have the social and economic human rights laid out in the Universal Declaration of Human Rights been so neglected or rejected, especially by the U.S.  Second, how has American foreign policy used and abused human rights.  Third, why have liberal or humanitarian interventions of a militarized sort become so prevalent since the end of the Cold War and why are they so damaging.  The goal is to get students to look critically at the meaning and uses of human rights, about which many display a naive enthusiasm.